Slow cinema and contemplative politics: radical documentary in the twenty-first century. Issue 3 (2nd September 2019) - Hamblin, Sarah
ABSTRACT: This essay positions Eric Baudelaire's The Anabasis of May and Fusako Shigenobu, Masao Adachi, and 27 Years without Images as part of a new phase of radical documentary practice for the twenty-first century. While Anabasis takes on the form of the essay film as a means of reviving the sense of internationalism and non-teleological revolutionary thought central to the political philosophies of the long 1960s, its tone differs substantially from this earlier wave of radical documentary films, abandoning the urgent calls to action or the familiar notions of spectatorial engagement and active participation that have come to define the radical documentary tradition. Instead, Anabasis is a slow film of contemplation, its languid pace tied to its pedagogical aims. Drawing on the Japanese radical documentary practice of fûkeiron, the film uses slowness to train its spectator to see politically, that is, to once again perceive the world through a radical lens and to thus recover the political vision that was the foundation of the long 1960s as the first step towards restoring the possibility of resistance in an age with neither a people nor a cause.